1998
DOI: 10.1677/jme.0.0200193
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of genes for aromatase and estrogen receptor during the gonadal development in chicken embryos

Abstract: In birds, differentiation of embryonic gonads is not as strictly determined by the genetic sex as it is in mammals, and can be influenced by early manipulation with a sex steroid hormone. Thus administration of an aromatase inhibitor induces testis development in the genetic female, and administration of estrogen induces a left ovotestis in the genetic male embryo. Another feature of avian gonadogenesis is that only the left ovary develops in most species. Molecular mechanisms underlying these features at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
108
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(117 citation statements)
references
References 25 publications
8
108
0
1
Order By: Relevance
“…These investigations revealed that cFoxL2 protein distribution was restricted to the medullar part of the ovary during early development. The same region of expression has been reported for aromatase transcripts Nakabayashi et al, 1998;Nishikimi et al, 2000;Oreal et al, 2002) and for the aromatase protein (Smith et al, 2003). The double immunolocalization of cFoxL2 and aromatase proteins to the sections of the left female gonad at E14 in our study demonstrated that cFoxL2 and aromatase proteins are expressed in the same cells.…”
Section: Foxl2 and Ovarian Differentiation In Chickensupporting
confidence: 87%
See 1 more Smart Citation
“…These investigations revealed that cFoxL2 protein distribution was restricted to the medullar part of the ovary during early development. The same region of expression has been reported for aromatase transcripts Nakabayashi et al, 1998;Nishikimi et al, 2000;Oreal et al, 2002) and for the aromatase protein (Smith et al, 2003). The double immunolocalization of cFoxL2 and aromatase proteins to the sections of the left female gonad at E14 in our study demonstrated that cFoxL2 and aromatase proteins are expressed in the same cells.…”
Section: Foxl2 and Ovarian Differentiation In Chickensupporting
confidence: 87%
“…Estrogens seem to play a crucial role in cortex formation and germ cell and supporting cell proliferation. The right chicken ovary lacking expression of estrogen receptors has a very thin cortex and regresses (Nakabayashi et al, 1998). In contrast, the left gonad develops into a functional ovary.…”
Section: Introductionmentioning
confidence: 99%
“…) females, expression is also turned off in the right gonad. (32,35) Taken together, these data indicate that estradiol synthesised in the medulla of female gonads mediates female sex determination by stimulating development of the cortex through ERa. Transient expression of ERa in ZZ embryos explains the susceptibility of males to feminisation by exogenous estradiol.…”
Section: Z Dosage or Dominant W?mentioning
confidence: 70%
“…(30,31) Conversely, ZZ males treated with estradiol become feminised, although this is not permanent. The two terminal enzymes necessary for estrogen synthesis, P-450aromatase and 17bHSD, are expressed only in ZW female gonads at the onset of morphological differentiation (day 6-6.5; stage 29-30) (32)(33)(34) (Fig. 4).…”
Section: Z Dosage or Dominant W?mentioning
confidence: 99%
“…Estrogen was reported to play a role in sex determination and gonadal differentiation in birds (Smith & Sinclair, 2004). Strikingly, estrogen and its receptor are asymmetrically expressed in avian embryonic gonads during sexual differentiation Nakabayashi et al, 1998). Asymmetric expression of estrogen and its receptor in chicken embryonic gonads is related to left-right gonadal asymmetry in birds (Intarapat & Stern, 2014).…”
Section: Introductionmentioning
confidence: 99%